Global and Chinese trends in acute myeloid leukemia burden (1990–2021): a comprehensive analysis based on the GBD study - Lu, Xiaojing; Peng, Xin; Zhang, Yunxiang; Zhu, Hongming; Zheng, Yu; Sun, Yue; Ji, Heyu; Li, Junmin; Jin, Haijiao; Li, Xiaoyang (Frontiers in Medicine, 2025)
BackgroundAcute myeloid leukemia (AML) poses a significant global health burden. This study evaluates long-term trends in AML burden from 1990 to 2021, focusing on global and Chinese patterns using Global Burden of Disease (GBD) data.MethodsWe extracted AML-related mortality, incidence, prevalence, and disability-adjusted life years (DALYs) from the GBD 1990–2021 dataset. Age-standardized rates (ASRs) were analyzed using Joinpoint regression to calculate annual percentage change (APC) and average APC (AAPC). Contributions of smoking, high body mass index (BMI), and occupational exposures were also evaluated.ResultsGlobally, AML deaths rose by 73.8%, with a 17.45% increase in ASMR. Conversely, China's ASMR declined by 14.76%. DALYs showed a global AAPC of −0.83%, with a sharper decline in China (−2.40%). Males and older adults (>65 years) bore a disproportionate burden. Smoking remained the top risk factor, while high BMI showed the fastest growth in attributable burden.ConclusionWhile AML's absolute burden is increasing worldwide, age-adjusted metrics are stabilizing or declining in China, likely due to healthcare improvements. Targeted prevention, risk control, and geriatric-oriented AML strategies are urgently needed.